(untitled) (Acta Scientiarum. Biological Sciences, 2020)
This study aimed to evaluate the cytotoxicity and genotoxicity and determine the LC50 concentration of powdered infant formulas widely marketed in South American countries. To this, milk samples, called as A, B, C and D, were analyzed in root meristem cells of Allium cepa, at concentrations of 0.075; 0.15 and 0.30 g mL-1, for 24 and 48 hours; and through cell viability in culture of normal line cells, via MTT test, for 24 hours, in the concentrations 0.018; 0.0375; 0.075 and 0.15 g mL-1. In A. cepa, all dairy products in the three concentrations caused significant inhibition of cell division in the meristems within the first 24 hours of exposure. In the in vitro evaluation, all milk formulas at 0.15 g mL-1, as well as milk A at a concentration of 0.037 g mL-1, C at 0.075 g mL-1 and D at 0.037 g mL-1, significantly reduced the cellular viability of the cell culture exposed to the foods studied, being potentially toxic. The milk A was considered the most toxic, with LC50 of 0.031 g mL-1, and B as the least toxic, with LC50 of 0.15 g mL-1. Therefore, the milk evaluated caused significant instability in cells of the test systems used and were characterized as cytotoxic.